Blood Pressure and Oxygen Saturation Post Deep Breathing Exercise and Head Up in Stroke Patients - Novita Nirmalasari; Rizqi Wahyu Hidayati (Jurnal Kesehatan Masyarakat, 2025)
According to Basic Health Research (Riskesdas) data from the last 12 years, the prevalence of strokes in Indonesia is still relatively high. Hypertension prevention aims to keep blood pressure under control. Non-pharmacological management is also required to supplement pharmacological therapy. Deep breathing exercises and head-up 30 degrees are two interventions that can be implemented. This study aimed to measure the influence of deep breathing exercises and head up 30 degrees on stroke patients’ oxygen saturation and blood pressure. This research used a quasi-experiment with a pretest-posttest control group design involving the recruitment of 60 respondents using a consecutive sampling technique. Head-up 30-degree positions and continuous deep breathing were measured using a digital sphygmomanometer, protractor, and oximeter. Data were analyzed using Wilcoxon and Mann-Whitney. The results showed that there was a significant difference in systolic blood pressure which was p=0.000 (p <0.005), and oxygen saturation showed p=0.001 (p <0.005). But there was no significant difference in diastolic blood pressure which was p=0.836 (p> 0.005). Deep breathing exercises and head-ups 30 degrees help control blood pressure in stroke patients.